Islamic wealth management : analysis of estate distribution practices and mechanisms in Singapore - Sadali Rasban
This research covers various estate distribution mechanisms and processes. The estate accumulated can be categorised as a non-estate asset or an estate asset. The purpose of this research is to understand the challenges faced by Muslims domiciled in Singapore on the distribution of those estate accumulated or created upon death within state laws of Singapore. These state laws comprise of Common law, Civil law and Muslim law. This research will assist in defining those estates as a non-estate asset or an estate asset. Categorising those estates as a non-estate asset or an estate asset is of prime importance, as it will define the estate distribution mechanisms and its processes that will be applicable. Singapore is a secular state with multi religions, races and cultures. Malays are the indigenous people of Singapore as stated in the Constitution of The Republic of Singapore (Singapore Parliament, 1965, a152.2) and a minority in Singapore. They are a dominant race among the Sunni Muslims of the Shafi'i madhhab. Though Singapore adopted English law (Common law and Civil law) after its independence on 9th August 1965, through the statue, Administration of Muslim Law Act (AMLA, cap 3), Muslim law is still practised as a personal law. AMLA limits the application of Muslim law in estate matter; for example, the ambit of MUIS and Syariah Court is to give an opinion on estate matters. Definition and application of Muslim law and its relevant terms, like estate, will be with the civil courts. There is also a lack of contemporary Muslim law experts and academic material in English that can are engageable as a reference by relevant authorities to understand the application of Muslim law on estate distribution in the Singapore context. This research adopts a qualitative approach, involving library research and content analysis of academic materials, court cases and case studies. It seeks to expose those challenges, discovers their root cause and offers practical Shari'ah compliant solutions for estate distribution within state laws. The outcome is to propose an innovative application of the estate distribution mechanisms and practices that are in harmony with state laws for equitable and just estate distribution. Finally, we recommend a proposal for the authorities to adopt the findings of this research, including the creation of a new profession to serve the community in matters about estate planning, estate distribution mechanisms and the distribution process to achieve the Shari'ah Objectives.